Snagovi jegyzetek : gondolatok, emlékezések 1956-1957 - Nagy Imre ; felelős szerk., bev., jegyz. Vida István. (Gondolat ; Nagy Imre Alapítvány, 2006)
Includes bibliography and indexes, p. 419-443. The CD-ROM supplement includes digitized copy of the manuscript.